Determinant Taxpayers’ Compliance among Micro, Small, and Medium-Scale Enterprises In Jakarta, Indonesia - Dewi Hargiyanti; Eva Herianti; Amor Marundha (Journal of Governance Risk Management Compliance and Sustainability, 2022)
Micro, small, and medium-scale enterprises (MSMEs) are business sectors known to significantly contribute to employment. Therefore, it is necessary to enhance tax compliance among MSME players as they are reported to contribute to GDP by 60%. This study aims to analyze the effect of the tax fairness dimensions, self-assessment system, and income level on tax compliance among MSMEs in Thamrin City, Southeast Asia’s largest shopping center located in Jakarta, Indonesia. This research is a quantitative study using primary data by distributing questionnaires from May until August 2021 to taxpayers. To this end, a quantitative method was applied by collecting primary data from taxpayers then respondents in this study were recruited using the purposive sampling technique (n=95). The data were analyzed using SEM PLS with SmartPLS 3.0, showing that tax fairness dimensions (p-value of 0,014), self-assessment system (p-value of 0,019), and income level (p-value of 0,000). These results explain that the tax fairness dimension has a significant effect on Taxpayers' Compliance, the self-assessment system has a significant effect on Taxpayers' Compliance, a self-assessment system has a significant effect on Taxpayers' Compliance.